European trends in the development of adult education (Pedagogy of Higher and Secondary Education, 2012)
Mishchenko O. M. European trends in the development of adult education.The article describes some international trends at adult education development on the level of category, practice, history and comparative-education. The role of adult education in development of positive trends in social life is highlighted at the article either, main attention here is attracted to the importance of comparative research in the field of adult education.
Keywords: comparative investigations in the adult education area; content of adult education; specific of the adult education